Notizie sul «Regesto gramsciano» di Alberto M. Cirese - Testa, Eugenio (International Gramsci Journal, 2023)
Between 1975 and 1985, Alberto M. Cirese coordinated a research group formed by scholars from the Universities of Cagliari, Ferrara, Rome, Siena and Turin, the goal of which was to build a lexicon of terms and concepts used by Antonio Gramsci in his Prison Notebooks, and which would be of importance for anthropological studies. The project was named the “Regesto gramsciano” (“Gramscian register”) since the researchers had the primary task of retrieving all the occurrence of the terms chosen and then photocopying them. The work produced a large number of index cards, related to some dozens of lemmas, but was never completed. A copy of the card collection is now held by the Universities of Cagliari and Turin and “La Sapienza” University of Rome.